The Effect of Problem Based Learning (PBL) Learning Model on Science Learning Outcomes at Grade V of State Elementary School 094126 Naga Dolok - Frendi Martuahman Damanik; Muktar Bahruddin Panjaitan; Theresia Monika Siahaan (International Journal of Technology and Education Research, 2026)
This study aimed to determine the effect of the Problem Based Learning (PBL) model on the IPAS learning outcomes of Grade V students at SD Negeri 094126 Naga Dolok. The background of this research was the low learning outcomes and limited student participation during the IPAS learning process, which were mainly caused by the use of conventional teacher-centered learning methods. Therefore, an innovative and student-centered learning model was needed to improve students’ understanding and engagement in learning. This study employed a quantitative approach using a pre-experimental design with the One Group Pretest-Posttest Design model. The population and sample consisted of all 28 Grade V students at SD Negeri 094126 Naga Dolok, selected using total sampling techniques. Data were collected through pretest and posttest instruments, while data analysis was conducted using a paired-sample t-test to determine the significance of differences before and after treatment. The results showed that the average pretest score was 68.52, indicating that students’ initial learning outcomes were still relatively low. After the implementation of the Problem Based Learning model, the average posttest score increased significantly to 90.26, and all students achieved the Minimum Completeness Criteria (KKM). The paired-sample t-test analysis revealed a significance value of 0.000 < 0.05, indicating a significant effect of the Problem Based Learning model on students’ learning outcomes. In conclusion, the Problem Based Learning model effectively improved the IPAS learning outcomes of Grade V students at SD Negeri 094126 Naga Dolok. In addition, the model enhanced students’ active participation, critical thinking, and collaborative learning skills during the learning process.